1997
DOI: 10.1021/jp9639915
|View full text |Cite
|
Sign up to set email alerts
|

Charge Carrier Dynamics at TiO2 Particles:  Reactivity of Free and Trapped Holes

Abstract: Details of the mechanism of the photocatalytic oxidation of the model compounds dichloroacetate, DCA-, and thiocyanate, SCN-, have been investigated employing time-resolved laser flash photolysis. Nanosized colloidal titanium dioxide (TiO2, anatase) particles with a mean diameter of 24 Å were used as photocatalysts in optically transparent aqueous suspensions. Detailed spectroscopic investigations of the processes occurring upon band gap irradiation in these colloidal aqueous TiO2 suspensions in the absence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
405
4
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 467 publications
(454 citation statements)
references
References 36 publications
41
405
4
4
Order By: Relevance
“…In methanol, where higher concentrations are achieved (25 mM), there are clear dynamics which persist to the maximum pumpprobe time delays. These observations are consistent with previous studies on isolated TiO 2 nanoparticles in solution [37][38][39]. In the low concentration regime, TiO 2 displays ultrafast relaxation, likely through the generation and subsequent trapping of surface electrons.…”
Section: Discussionsupporting
confidence: 92%
“…In methanol, where higher concentrations are achieved (25 mM), there are clear dynamics which persist to the maximum pumpprobe time delays. These observations are consistent with previous studies on isolated TiO 2 nanoparticles in solution [37][38][39]. In the low concentration regime, TiO 2 displays ultrafast relaxation, likely through the generation and subsequent trapping of surface electrons.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have shown that this contribution can be assigned to the absorption of the injected electron itself. [30][31][32] The temporal characteristics in this range are exemplified by the curve obtained at λ pr ) 742 nm ( Figure 9, lower trace): the initial absorbance increase occurs within the experimental time resolution. The signal decreases very fast to a positive offset, which remains constant from 10 ps to 1 ns.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies highlight the presence of both shallowly and deeply trapped holes on the photocatalyst surface [115,116]. Shallowly trapped holes show reactivity and mobility comparable to free ones, reacting thus very rapidly with chemisorbed species.…”
Section: Photoreforming Of Alcoholsmentioning
confidence: 99%